2018
DOI: 10.1002/esp.4533
|View full text |Cite
|
Sign up to set email alerts
|

Investigating plant root effects on soil electrical conductivity: An integrated field monitoring and statistical modelling approach

Abstract: Plants have been shown to affect soil water content and temperature. Previous studies were conducted mainly in forestry and agricultural soils, where conditions of soil and vegetation are different from those in an urban landscape. In an urban landscape, the influence of plant roots on electrical conductivity, soil water content and temperature is still not clear. This study aims to investigate the effects of soil water content and temperature on electrical conductivity in vegetated soils through an integrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…(b) Electrical resistivity (ρ) vs. percentage volumetric water content (WC) from Figure 2 and Figure 5 of Ni et al. (2018). (c) Frequency averaged resistivity magnitude (|ρ|) as a function of percentage volumetric water content of Mary et al.…”
Section: Methods Targeting Electrical Resistivitymentioning
confidence: 99%
“…(b) Electrical resistivity (ρ) vs. percentage volumetric water content (WC) from Figure 2 and Figure 5 of Ni et al. (2018). (c) Frequency averaged resistivity magnitude (|ρ|) as a function of percentage volumetric water content of Mary et al.…”
Section: Methods Targeting Electrical Resistivitymentioning
confidence: 99%
“…The negative impact of excess Na + and/ or Cl − on plants is addressed as salt stress (Munns 2005 , also pose adverse influences on crop growth. Salt stress affects major processes of various plants, such as germination (Bybordi 2010; Fernández-Torquemada and Sánchez-Lizaso 2013; Khodarahmpour et al 2012), growth (White and Broadley 2001;Xu et al 2000), photosynthesis (Kalaji et al 2011;Saha et al 2010), nutrient imbalance (Hu and Schmidhalter 2005;Rogers et al 2003), and final yield (Garg et al 2015a;Ni et al 2018). Plant roots are restricted by the salinity stress, which can be attributed to the facts that (1) the existing salt reduces water absorption capacity of plants and further leads to reductions in growth and (2) the injured cells in the plant tissue resulted from excessive salt lead to reductions in growth.…”
Section: Effects Of Salts On Groundwater Evaporationmentioning
confidence: 99%
“…However, there was a quantitative relationship among the three factors. According to the statistical modelling theory proposed by scholars when studying the effect of plant roots on soil conductivity to determine the magnitude of soil conductivity [22], the following relational model was derived:…”
Section: The Relationship Between the Conductivity Of Clay With Adnbmentioning
confidence: 99%
“…Therefore, finding the trends and the mechanisms of soil conductivity changes under different temperature conditions is a simple, effective and low-cost way to study the effect of soil amendment on ecological restoration and improve the performance of a soil amendment. Ni et al integrated a field monitoring and computational modelling approach, then found the effects of soil water content and temperature on electrical conductivity in vegetated soils and built a model that could predict nonlinear relationships between electrical conductivity and soil temperature and water content [22]. Our model was based on the foundation.…”
Section: Introductionmentioning
confidence: 99%